PENGEMBANGAN MODUL MULTIMEDIA INTERAKTIF BERBASIS E-LEARNING PADA POKOK BAHASAN BESARAN DAN SATUAN DI SMA - Tri Wahyuni; Sri Wahyuni; Yushardi Yushardi (JURNAL PEMBELAJARAN FISIKA, 2017)
This research was the development research to produce multimediainteractive modules based e-learning on the subject amount and units in senior highschool that aimed to: 1) validation of multimedia interactive modules, 2) theeffectiveness of learning, and 3) learning outcomes. The results of this researchwere: validation expert multimedia interactive modules based on e-learning reached3,95 with a valid enough category and validation user reached 4,38 with a validcategory; result of the effectiveness of learning as value of validation audiencereached 67,62 with valid category or can be used with small revision; and result oflearning outcomes reached 84,72 with high categories.Key words: module, multimedia interactive, e-learning